ASI eksklusif dan berat lahir berpengaruh terhadap stunting pada balita 2-5 tahun di Kabupaten Pesawaran - Apri Sulistianingsih; Rita Sari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Stunting cases in infants in Indonesia continue to be a maternal and child health problem. Stunting cases in Pesawaran District increase every year. Some of the factors that influence the incidence of stunting in children include the history of exclusive breastfeeding and low birth weight (LBW) babies.Objective: This study aims to determine the effect of exclusive breastfeeding and birth weight on stunting in children 2-5 years cases in Pesawaran District.Method: This research used observational analytics with a cross-sectional approach. This research was conducted in March-May 2017 in 12 Puskesmas on Pesawaran Lampung District. The number of samples was 385 samples. The variables studied in this study were the incidence of stunting, history of LBW and history of exclusive breastfeeding. Analysis and present data using the Chi-Square test and multiple logistic regression.Results: Children with a history of LBW (OR=12.30; 95% CI:3.663-41.299) and exclusive breastfeeding history (OR=0.122; 95% CI:0.075-0.199) were significantly associated with the incidence of stunting. The multivariate analysis explained the history of exclusive breastfeeding with OR=0.108 (CI 95%: 0.065-0.180) and birth weight with OR=17.063 (CI 95%: 4.892-59.511).Conclusion: Children with exclusively breastfeeding 9.3 times less risk for stunting than children non-exclusive breastfeeding or exclusive breastfeeding provides a protective effect against stunting in toddlers. Children with an LBW history had a risk of 17.063 times greater for stunting than children with normal birth weight.